Douglas fir biochar enriched with plant nutrients as a controlled release fertilizer - Prashan M. Rodrigo; Jac J. Varco; Beatrice Arwenyo; Mary G. Paganucci; Hashani P. Abeysinghe; Joshua A. Hartley; Allie C. Davis; Chanaka M. Navarathna; Rooban V.K.G. Thirumalai; Xuefeng Zhang; Charles U. Pittman, Jr.; Todd E. Mlsna (Soil Advances)
Numerous agricultural soils may lack essential macronutrients crucial for plant growth. Utilizing highly water-soluble commercial fertilizers over extended periods can be both expensive and ecologically unfavorable. Herein, we developed nitrogen (N), phosphorus (P), potassium (K), and magnesium (Mg)-enriched Douglas fir biochar (BCF) as an eco-friendly and cost-effective fertilizer for plants. The BCF was synthesized by precipitating MgNH4PO4.6 H2O and MgKPO4.6 H2O on the biochar surface, which was characterized using XRD, XPS, SEM, and elemental analysis. BCF contained 43.76 ± 3.26 mg g−1 of NH4+ (3.40 ± 0.25 as N%), 120.14 ± 5.95 mg g−1 of PO43- (8.98 ± 0.31 as P2O5%), 3.79 ± 0.58 mg g−1 of K+ (0.41 ± 0.01 as K2O%), and 34.05 mg g−1 of Mg2+. The releasing behaviors of NH4+, PO43-, K+, and Mg2+ were investigated through a series of batch leaching experiments at different pHs (1−13), different water matrices, and three different temperatures (5, 25, and 40 °C), as well as fixed-bed continuous flow column experiments. Finally, greenhouse studies were carried out to study the performance of BCF fertilizer as a slow-release P fertilizer for corn growth. In comparison with conventional P fertilizer and the simple blends biochar (BC) and P fertilizer, the use of BCF yielded ∼23 % higher plant heights on the 35th day, ∼64 % higher plant dry weight, and ∼111 % higher P uptake compared to triple superphosphate fertilizer at 29.70 kg (P2O5) ha−1 nutrient rate for corn growth.